THE RELATIONSHIP BETWEEN THE USE OF INJECTABLE HORMONAL CONTRACEPTION AND THE INCIDENCE OF MELASMA IN WOMEN AGE 30-50 YEARS OLD AT SURANTIAH COMMUNITY HEALTH CENTER PESISIR SELATAN 2024-2025 - Irma Primawati; Atiqah Risyia; Irdawaty Izrul; Fitra Deny (Yayasan Nusantara Hasana Berdikari, 2026)
Ultraviolet light exposure and hormonal imbalances have been identified as the main causes of melasma. The use of hormonal contraceptives is also suspected to be a risk factor for melasma, through an imbalance of estrogen and progesterone hormones, which triggers increased skin pigmentation. Aims of this research to determine the relationship between the use of injectable hormonal contraceptives and the incidence of melasma in women aged 30-50 years old at the Surantiah Pesisir Selatan Community Health Center in 2024-2025. This study was an observational analytic study. The accessible population was women aged 30-50 years old using 1-month and 3-month injectable contraceptives who visited the Surantiah Pesisir Selatan Community Health Center between November 2024 and July 2025. The sampling technique used was purposive sampling. Univariate data analysis was presented in the form of frequency distributions, while bivariate analysis used the chi-square test. Data processing was performed using the computerized SPSS program IBM version 25.0. The highest age was 35-39 years old, namely 18 people (26.9%), the highest use of hormonal contraceptives was injectable progestin injections (3 months), namely 46 people (68.7%), the highest incidence of melasma was mild, namely 28 people (41.8%), the highest duration of use was 1-3 years and >3 years, namely 32 people (47.8%) and there is the relationship between the use of injectable hormonal contraceptives and the incidence of melasma in women aged 30-50 years old at the Surantiah Pesisir Selatan Community Health Center in 2024-2025 (p=0.022). There is the relationship between the use of injectable hormonal contraceptives and the incidence of melasma in women age 30-50 years old at the Surantiah Pesisir Selatan Community Health Center in 2024-2025.